Cerium-photocatalyzed aerobic oxidation of benzylic alcohols to aldehydes and ketones - Yedase, Girish Suresh; Kumar, Sumit; Stahl, Jessica; König, Burkhard; Yatham, Veera Reddy (Beilstein Journal of Organic Chemistry, 2021)
We have developed a cerium-photocatalyzed aerobic oxidation of primary and secondary benzylic alcohols to aldehydes and ketones using inexpensive CeCl3·7H2O as photocatalyst and air oxygen as the terminal oxidant.
Keywords: alcohol; aldehydes; cerium; oxidation; ketones; visible light